Impact of stakeholders on the development of non-governmental organisations in Slovenia - Mevlja, Bojan (Array, 2019)
Unlike profit organisations, which pursue profitable goals under the influence of influential stakeholders, the interests of stakeholders in nongovernmental organisations (NGOs) are much less uniform. The paper aims to focus on the contribution and the characteristics of non-governmental organisations (NGOs) in Slovenia, and the conflicting interests as well as the impact of internal and external stakeholders of NGOs. The purpose of this paper is to conduct an empirical analysis of the key infl uences of internal and external stakeholders. Our intention is to determine the relations between the interests of influential stakeholders and the performance of the organisations in question, as well as to define the understanding of performance from the viewpoint of NGOs’ management. We confirmed the hypothesis proposing that the external influences of stakeholders have a greater impact on the performance than the internal infl uences. We found out that public relations, advocacy, fundraising and regularity have a statistically significant influence on the NGOs’ mission. Complexity and heterogeneity of non-governmental organisations could be counted among the most important research limitations. From the aspect of scientific contribution in the geographical area of Central Europe, i.e. a former communist state, a country in transition economy, it was thus far impossible to find contributions to empirically examine the impact of stakeholders on the development of nongovernmental organisations; therefore, the study described in the article is unique in this area.